Determinan Audit Report Lag pada Perusahaan Property dan Real Estate yang Terdaftar di BEI Tahun 2018-2021 - Agra Belva Harelya; Nelvirita Nelvirita (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to examine the effect of firm complexity, auditor reputation and company age on the audit report lag. The population is property and real estate sector companies listed on the Indonesia Stock Exchange in 2018-2021. The sampling technique used is purposive sampling method and acquired 185 companies. The statistical method uses multiple linear regression analysis. The results show that auditor reputation and company age has no effect on audit report lag, firm complexity positively affects audit report lag property and real estate sector companies listed on the Indonesia Stock Exchange in 2018-2021.